Exploring the relationship between coronary heart disease and type 2 diabetes: a cross-sectional study of secondary prevention among diabetes patients - Gjelsvik, Bjørn E.; Tran, Anh Thi; Berg, Tore Julsrud; Bakke, Åsne; Mdala, Ibrahimu; Nøkleby, Kjersti; Cooper, John G.; Claudi, Tor; Løvaas, Karianne Fjeld; Thue, Geir; Sandberg, Sverre; Jenum, Anne Karen (BJGP Open, 2020)
Background: Coronary heart disease (CHD) and stroke are the major causes of death among people with diabetes. Aim: To describe the prevalence and onset of CHD and stroke among patients with type 2 diabetes mellitus (T2DM) in primary care in Norway, and explore the quality of secondary prevention. Design & setting: A cross-sectional study of data was undertaken from electronic medical records (EMRs) of 10 255 patients with T2DM in general practice. The study took place in five counties of Norway (Oslo, Akershus, Rogaland, Hordaland, and Nordland). Quality of care was assessed based on national guideline recommendations. Method: Summary statistics with adjustments and binary logistic regression models were used. Results: In total, 2260 patients (22.1%) had CHD and 759 (7.4%) had stroke. South Asians had significantly more CHD than ethnic Norwegians (29.5%, 95% confidence interval [CI] = 26.1 to 33.0 versus 21.5%, CI = 20.6 to 22.3) and other ethnic groups, and experienced onset of CHD or stroke at a mean of 7 years before Norwegians. In 47.9% of the patients, CHD was diagnosed before T2DM. Treatment target for low-density lipoprotein (LDL) cholesterol was reached for 30.0% and for systolic blood pressure (SBP) for 65.1% of the patients with CHD. Further, 20.9% of patients with CHD were present smokers, and only 5.0% of patients reached all four treatment targets (no smoking, HbA1c ≤7.0%, SBP <135 mmHg, LDL-cholesterol <1.8 mmol/l). Conclusion: The diagnosis of CHD preceded the diagnosis of T2DM in half of the patients. The prevalence of CHD was highest and onset earlier among ethnic South Asians. More intensive treatment of lipids, blood pressure, and smoking are needed in patients with T2DM and CHD. publishedVersion